Pilocarpine dispensation for the soft hydrophilic contact lens. - Ruben, M (1975)
The use of hydrophilic soft contact lenses for dispensation of pilocarpine is described. The release rate of pilocarpine from three materials of different water content was estimated and from this the surface concentrations were calculated. It is estimated that PolyHEMA can after 15 hours provide a 1 per cent surface concentration of pilocarpine, whereas higher water content materials (70 and 85 per cent) halve this, although they provide a much higher concentration in the first few hours of use. These results are based upon pre-soaking in 4 per cent pilocarpine solution. Because contact lenses present a management problem, this method of dispensation will be used only for selected cases. Some clinical examples treated successfully over a 20 month period are discussed.